2015
DOI: 10.1016/j.ihj.2015.10.380
|View full text |Cite
|
Sign up to set email alerts
|

The Indian consensus guidance on stroke prevention in atrial fibrillation: An emphasis on practical use of nonvitamin K oral anticoagulants

Abstract: The last ten years have seen rapid strides in the evolution of nonvitamin K oral anticoagulants (NOACs) for stroke prevention in patients with atrial fibrillation (AF). For the preparation of this consensus, a comprehensive literature search was performed and data on available trials, subpopulation analyses, and case reports were analyzed. This Indian consensus document intends to provide guidance on selecting the right NOAC for the right patients by formulating expert opinions based on the available trials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 112 publications
0
10
0
1
Order By: Relevance
“…NOACs are more expensive in comparison with VKA; however, in the long term, NOACs might prove to be the more cost-effective treatment choice compared with VKA treatment, 23 primarily because of lower monitoring costs and reduced numbers of patients with stroke and SE 22 . Practical guidelines on the management of stroke prevention in AF (SPAF) with NOACs in Asians, including Indians, have been published recently by Dalal et al 24 for the SPAF Academy India experts. Unlike many countries, the GARFIELD-AF registry has not observed any definitive increase in NOACs prescribing in India over time (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NOACs are more expensive in comparison with VKA; however, in the long term, NOACs might prove to be the more cost-effective treatment choice compared with VKA treatment, 23 primarily because of lower monitoring costs and reduced numbers of patients with stroke and SE 22 . Practical guidelines on the management of stroke prevention in AF (SPAF) with NOACs in Asians, including Indians, have been published recently by Dalal et al 24 for the SPAF Academy India experts. Unlike many countries, the GARFIELD-AF registry has not observed any definitive increase in NOACs prescribing in India over time (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2,23,32,35,38,42,43 As doses subsequentes de DOACs devem ser tomadas pelo menos 6h após o procedimento (Nível Ib, Classe I). 23,32,35,38,44 Pergunta 3: Em doentes adultos a fazer TAG e/ou TAC existem medidas pré-operatórias de relevo que modifiquem a incidência de FTE?…”
Section: Resultsunclassified
“…This finding should prompt critical reevaluation of certain Asian guidelines which recommend lower INR ranges such as Japanese Circulation Society guidelines, the Asia Pacific Heart Rhythm Society, and Indian Consensus Guidance on Stroke Prevention in Atrial Fibrillation, which recommend INR ranges of 1.6 to 2.6 in elderly AF patients. [110][111][112] Despite many Asian guidelines recommending standard INR ranges, it has been reported that across Asia physicians often opt for lower INR targets as opposed to standard, especially in elderly patients. 5,113,114 In our sensitivity analysis evaluating studies that included patients at least 60 years of age, a lower INR target increased thromboembolism compared with standard INR ranges in East Asians.…”
Section: Discussionmentioning
confidence: 99%